Diet of land birds along an elevational gradient in Papua New Guinea - Sam, Katerina; Koane, Bonny; Jeppy, Samuel; Sykorova, Jana; Novotny, Vojtech (Scientific reports, 2017)
Food preferences and exploitation are crucial to many aspects of avian ecology and are of increasing importance as we progress in our understanding of community ecology. We studied birds and their feeding specialization in the Central Range of Papua New Guinea, at eight study sites along a complete (200 to 3700 m a.s.l.) rainforest elevational gradient. The relative species richness and abundance increased with increasing elevation for insect and nectar eating birds, and decreased with elevation for fruit feeding birds. Using emetic tartar, we coerced 999 individuals from 99 bird species to regurgitate their stomach contents and studied these food samples. The proportion of arthropods in food samples increased with increasing elevation at the expense of plant material. Body size of arthropods eaten by birds decreased with increasing elevation. This reflected the parallel elevational trend in the body size of arthropods available in the forest understory. Body size of insectivorous birds was significantly positively correlated with the body size of arthropods they ate. Coleoptera were the most exploited arthropods, followed by Araneae, Hymenoptera, and Lepidoptera. Selectivity indexes showed that most of the arthropod taxa were taken opportunistically, reflecting the spatial patterns in arthropod abundances to which the birds were exposed.
Keywords: Papua New Guinea; stravovací zvyklosti; Animals; ptáci; Birds; Feeding Behavior; zvířata; Papua Nová Guinea